Six unrecorded species of Russula (Russulales) from Nagaland, India and their nutrient composition - RAJESH KUMAR; ASHWANI TAPWAL; SHAILESH PANDEY; RAJA RISHI; GAURAV MISHRA; KRISHNA GIRI (Smujo International, 2014)
Abstract. Kumar R, Tapwal A, Pandey S, Raja-Rishi R, Mishra G, Giri K. 2014. Six unrecorded species of Russula (Russulales) from Nagaland, India and their nutrient composition. Nusantara Bioscience 6: 33-38. The young and matured carpophores of mushrooms were collected from the forests of Puliebzie, Zakhama, Pherma, Mankoi, Chungtia, and Tigit located in different districts of Nagaland, one of the north-eastern states of India. All the species were found associated with Pinus khasya, P. caribaea, P. patula, Cryptomeria japonica, Canarium resiniferum, Dipterocarpus macrocarpus, and Shorea assamica. The collected mushrooms were identified as Russula species on the basis of their macro and microscopic characteristics. The identified Russula species were also screened for their nutrient content. The protein and carbohydrate content was found to vary between 28.12 to 42.86, and 49.33 to 55%, respectively. These species [Russula aeruginea Lindblad; -Fr., R. alnetorum Romagnesi, R. brevipes Peck, R. fragrantissima Romagnesi, R. nobilis Velen. and R. ochroleuca (Pers.) Fr Gray.] are a new record from Nagaland state of India.